SARS-CoV-2 Vaccine–Induced Immune Thrombotic Thrombocytopenia - Rocha, Diana Isabel Soares Silva Moreira (2022)
The first vaccines against the SARS-CoV-2 virus appeared one year after the WHO declared COVID-19 as a pandemic, with data from United Kingdom and United States of America (USA) reporting a reduction in hospitalization about 67% e 94%, with one or two doses of an approved vaccine. In February 2021, the first cases of thrombocytopenia and thrombosis at uncommon sites (cerebral venous sinus and splanchnic venous thrombosis) induced by the vaccines were described. The incidence is still unknown, but early studies in the USA suggest an incidence of 1 in 533 333/vaccinated individuals, and this is probably underestimated. Although uncommon, it is a serious adverse effect with a high mortality rate, estimated at 20%. This case report highlights the need for a high level of suspicion, which may change the prognosis of some of these patients.